2021
DOI: 10.3389/fphys.2021.661464
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness: Effects of Anticancer Drugs Used for Breast Cancer Women

Abstract: Purpose: It is well known that anticancer drugs used for treating breast cancer can cause cardiac toxicity, and less is known about vascular toxicity. The aim of this study was to assess subclinical vascular effects of anthracyclines and trastuzumab (TRZ) in women treated for breast cancer.Methods: We enrolled 133 female patients with breast cancer undergoing adjuvant treatment with anthracycline-containing chemotherapy (CT) followed by taxane (paclitaxel/docetaxel) + TRZ. Patients underwent a standard echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…It has been recently recognised that DOX impairs vascular function [ 11 , 12 , 13 , 14 , 19 ], yet the exact mechanisms are not fully elucidated yet. While there is consensus about the detrimental effects of DOX on endothelium-dependent vasodilation [ 19 , 20 , 21 , 22 ], several studies have reported conflicting results on VSMC contraction [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently recognised that DOX impairs vascular function [ 11 , 12 , 13 , 14 , 19 ], yet the exact mechanisms are not fully elucidated yet. While there is consensus about the detrimental effects of DOX on endothelium-dependent vasodilation [ 19 , 20 , 21 , 22 ], several studies have reported conflicting results on VSMC contraction [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies point towards accelerated vascular ageing in childhood cancer survivors, as evidenced by a higher incidence of atherosclerosis and hypertension [ 8 , 9 , 10 ]. Moreover, several studies have demonstrated that DOX increases arterial stiffness in cancer patients, both during and after treatment [ 11 , 12 , 13 , 14 ]. Arterial stiffness is associated with an increased risk of cardiovascular events and mortality, as it impacts arterial pressure, cardiac performance and perfusion [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other cell types, such as endothelial cells, cardiac progenitor cells and cardiac fibroblasts, have been identified as potential additional targets, creating a more complex scenario in the pathogenesis of anthracycline-induced cardiotoxicity (Figure 1). Moreover, Novo et al [30] demonstrate an increase in arterial stiffness in patients treated with anthracyclines. Indeed, anthracycline-induced endothelial vascular damage might provoke structural acute vascular changes through the alterations of the vascular matrix and by interfering with the endothelial regulation of vascular smooth muscle cell tone by reducing nitric oxide synthesis.…”
Section: Anthracyclinementioning
confidence: 97%
“…All studies were published between 2010 and 2021 and included patients with solid tumors, such as breast cancer or sarcoma (35)(36)(37)(38)(39)(40), or hematologic malignancies, such as lymphoma and leukemia (35,36,39,(41)(42)(43), or a combination thereof (35,36,39). All studies were prospective with data provided from before treatment as well as after a follow-up period between 1 and 14 months (Figure 2).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Therefore, the effect of cancer itself, presence of CV risk factors or other confounding treatments and comorbidities could not be identified. Secondly, except for two studies (40,42), they were based on small numbers of participants, which explains the large CIs of some of the studies. Another limitation of this meta-analysis is that the assumption of a normal distribution has been made for PWV in the study by Novo et al,(40) even though data was indicated as median (IQR).…”
Section: Strengths and Limitationsmentioning
confidence: 99%